2021
DOI: 10.3390/ijgi10070458
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Accessibility-Based Model to Evaluate Educational Equity: A Case Study in the City of Wuhan

Abstract: Limited studies focus on educational equity from the spatial accessibility perspective. This study combines survey data and big data and proposes a multi-mode Huff two-step floating catchment area (MMH2SFCA) method to calculate accessibility while considering multiple travel modes and school attractiveness. This method can also calculate education quality by extending the accessibility in each community. Results show that our proposed method can reliably identify the accessibility differences of schools across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 87 publications
1
12
0
2
Order By: Relevance
“…Some studies have confirmed that citizens' actual routes and time consumption were more meaningful than Euclidean distance, and high travel costs may diminish residents' desire to visit parks [39,45]. Interestingly, we found that residents' usage patterns of the different parks were relatively consistent from the perspective of travel time consumption.…”
Section: Spatial Relationship Between Park Service Area and Accessibility Based On Time Thresholdssupporting
confidence: 60%
See 1 more Smart Citation
“…Some studies have confirmed that citizens' actual routes and time consumption were more meaningful than Euclidean distance, and high travel costs may diminish residents' desire to visit parks [39,45]. Interestingly, we found that residents' usage patterns of the different parks were relatively consistent from the perspective of travel time consumption.…”
Section: Spatial Relationship Between Park Service Area and Accessibility Based On Time Thresholdssupporting
confidence: 60%
“…In contrast to network analysis by ArcGIS, the latest road networks will no longer need to be established ahead of time. By inputting the latitude/longitude coordinates of the origin and destination with APIs, we could easily obtain detailed travel routes and the corresponding travel costs calculated by AI technology for different transportation modes, such as driving, public transit, walking, and biking [44][45][46]. Scholars have begun to use web map APIs in their studies, such as those on the dynamic efficiency of traffic networks [47] and the spatial equity of public facilities [48,49].…”
Section: Introductionmentioning
confidence: 99%
“…However, our results for the dynamic public transit mode are not entirely consistent, which may be due to our study considering the public transit mode (such as bus and metro) and set a smaller spatial scale unit. Public transit accessibility is more dependent on route and station distribution [28], so the comparison relationship is more complicated. In addition, a finer study scale may also make it easier to show data differences.…”
Section: Interpretation and Applicationmentioning
confidence: 99%
“…The original 2SFCA approach assumes that all populations travel to supply locations by a single travel mode [27]. This assumption may underestimate or overestimate the accessibility value and result in an unreliable research conclusion [28]. In fact, the mode of travel may be related to the location of the destination and may vary from person to person.…”
Section: Introductionmentioning
confidence: 99%
“…The 2SFCA method is an easy-to-explain and easy-to-calculate method and can be combined with geographic information systems (GIS) to determine existing differences that exist in terms of fairness [31,32]. This method has been widely used in research on public health services [7,33], public transport, education services [34,35], comprehensive public services [36,37], and other fields [27,[38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%